Conflicts of climate change mitigation actions with the sustainable development goals: Creating a systematic overview by the example of renewable energy technologies - Jan-Hendrik Scheyl (Wuppertal Institut für Klima, Umwelt, Energie, 2020)
Despite a strong connection between the Paris Agreement and the 2030 Agenda for Sustainable Development, climate change mitigation actions and sustainable development objectives are oftentimes not aligned efficiently, causing conflicts between the objectives. This thesis creates a systematic overview of conflicts of three renewable energy technologies with the Sustainable Development Goals (SDGs) by a literature review in Web of Science. The technologies solar energy, wind energy and hydropower function as examples for climate change mitigation actions. Out of 530 screened articles, 63 demonstrated conflicts. The systematic overview reveals that conflicts are different for each technology, but conflicts in regard to biodiversity loss and the degradation of natural habitats (SDG 15) and inequalities (SDG 10) were frequently identified for all technologies. The results of the systematic overview suggest that the site selection and the decision-making process on the construction of renewable energy projects are crucial stages to avoid conflicts with the SDGs. – – Trotz eines engen Zusammenhangs zwischen dem Pariser Abkommen und der 2030 Agenda, sind Ziele des Klimaschutzes und Ziele der nachhaltigen Entwicklung oft nicht effizient aufeinander abgestimmt. Dies kann zu Konflikten zwischen den Zielen führen. Diese Arbeit erstellt einen systematischen Überblick über Konflikte von drei Technologien erneuerbarer Energien mit den Zielen nachhaltiger Entwicklung (SDGs) durch eine Literaturrecherche im Web of Science. Die Technologien Solarenergie, Windenergie und Wasserkraft dienen als Beispiele für Ziele des Klimaschutzes. Von 530 überprüften Artikeln zeigten 63 Konflikte. Der systematische Überblick zeigt, dass Konflikte für jede der Technologien unterschiedlich sind. Besonders stechen jedoch Konflikte im Hinblick auf den Verlust der biologischen Vielfalt und die Zerstörung natürlicher Lebensräume (SDG 15) und Ungleichheiten (SDG 10) auf. Die Ergebnisse des systematischen Überblicks deuten darauf hin, dass die Standortwahl und der Entscheidungsprozess über den Bau von Projekten im Bereich der erneuerbaren Energien entscheidende Schritte sind, um Konflikte mit den SDGs zu vermeiden.
urn:nbn:de:bsz:wup4-opus-74720
Keywords: 330